Exoplanetary oxygen fugacities from polluted white dwarf stars. Issue Volume 15:Issue S357(2019) (October 2019) - Doyle, Alexandra E.; Klein, Beth; Zuckerman, Ben; Schlichting, Hilke E.; Young, Edward D.
Abstract: The intrinsic oxygen fugacity of a planet profoundly influences a variety of its geochemical and geophysical aspects. Most rocky bodies in our solar system formed with oxygen fugacities approximately five orders of magnitude higher than that corresponding to a hydrogen-rich gas of solar composition. Here we derive oxygen fugacities of extrasolar rocky bodies from the elemental abundances in 15 white dwarf (WD) stars polluted by accretion of rocks. We find that the intrinsic oxygen fugacities of rocks accreted by the WDs are similar to those of terrestrial planets and asteroids in our solar system. This result suggests that at least some rocky exoplanets are geophysically and geochemically similar to Earth.